Treatment and Diagnostic Problems of Pneumonia in Children (Texas Journal of Medical Science, 2023)
Pneumonia in children is one of the most common, serious, potentially life-threatening diseases. The criteria for the diagnosis and treatment of pneumonia have been developed a long time ago and are clearly formulated. However, one has to deal with underdiagnosis and irrational therapy, which is observed more often at the outpatient stage. A comparative analysis of recommendations published recently in a number of countries on the diagnosis and treatment of pneumonia in children was carried out. We studied the timeliness of diagnosis and the adequacy of therapy at the outpatient stage in 167 hospitalized children with pneumonia.